2022
DOI: 10.1136/jitc-2021-004026
|View full text |Cite
|
Sign up to set email alerts
|

eEF2K promotes PD-L1 stabilization through inactivating GSK3β in melanoma

Abstract: BackgroundImmune checkpoint blockade (ICB) targeting programmed death ligand-1 (PD-L1)/programmed cell death protein-1 (PD-1) pathway has become an attractive strategy for cancer treatment; however, unsatisfactory efficacy has limited its clinical benefits. Therefore, a more comprehensive understanding of the regulation of PD-L1 expression is essential for developing more effective cancer immunotherapy. Recent studies have revealed the important roles of eukaryotic elongation factor 2 kinase (eEF2K) in promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The primary role of eukaryotic elongation factor 2 (eEF2) is to participate in the elongation phase of protein synthesis, with the phosphorylation of eEF2 representing a key mechanism in this phase. Eukaryotic elongation factor 2 kinase (eEF2K) is the exclusive protein kinase known to phosphorylate eEF2 at the 56th threonine residue (Thr-56, p-eEF2) (Chen et al, 2022). Studies indicate that eEF2K is expressed in neurons and may contribute to processes such as learning, memory, and depression (Klupt and Jia, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The primary role of eukaryotic elongation factor 2 (eEF2) is to participate in the elongation phase of protein synthesis, with the phosphorylation of eEF2 representing a key mechanism in this phase. Eukaryotic elongation factor 2 kinase (eEF2K) is the exclusive protein kinase known to phosphorylate eEF2 at the 56th threonine residue (Thr-56, p-eEF2) (Chen et al, 2022). Studies indicate that eEF2K is expressed in neurons and may contribute to processes such as learning, memory, and depression (Klupt and Jia, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inhibition of β‐TrCP or certain special molecules that inactivate GSK3β could in turn block PD‐L1 ubiquitination, promote its stability, and eventually, induce cancer immunosuppression. Recently, we found that eukaryotic elongation factor 2 kinase (eEF2K) promotes immunosuppression through GSK3β inactivation‐mediated PD‐L1 stabilization in melanoma, providing a potential combinational therapeutic strategy to enhance the efficacy of immunotherapy 83 . The CKLF‐like MARVEL transmembrane domain‐containing protein 6 (CMTM6), which is expressed on the cell surface, colocalized with PD‐L1 at the plasma membrane to interrupt PD‐L1 ubiquitination and prolong its half‐life, and as a result, enhanced the capacity of cancer cells to escape immune surveillance.…”
Section: Ubiquitination Machinery In the Regulation Of Tumor Microenv...mentioning
confidence: 99%
“…Recently, we found that eukaryotic elongation factor 2 kinase (eEF2K) promotes immunosuppression through GSK3β inactivation-mediated PD-L1 stabilization in melanoma, providing a potential combinational therapeutic strategy to enhance the efficacy of immunotherapy. 83 The CKLF-like MARVEL transmembrane domain-containing protein 6 (CMTM6), which is expressed on the cell surface, colocalized with PD-L1 at the plasma membrane to interrupt PD-L1 ubiquitination and prolong its half-life, and as a result, enhanced the capacity of cancer cells to escape immune surveillance. CMTM6 depletion improved PD-L1 mediated Tcell suppression, highlighting potential values of CMTM6 as a therapeutic target or in enhancing the efficacy of the present PD-L1/PD-1 blocking therapies.…”
Section: Pd-l1mentioning
confidence: 99%
“…More importantly, anti-PD-1 and GSK-3 inhibitor combinations may be effective to treat solid tumors that are otherwise unresponsive to immune checkpoint blockade. This is likely because, GSK-3β phosphorylates PD-L1 in tumor cells to induce its degradation, and GSK-3β inactivation can be seen in some cancers to stabilize PD-L1 expression ( 116 , 117 ). Similarly, inhibiting GSK-3β with the chemotherapy-sensitization combination disulfiram and copper stabilizes PD-L1 expression in a hepatocellular carcinoma model ( 118 ).…”
Section: Gsk-3mentioning
confidence: 99%